Long Narrative Songs from the Mongghul of Northeast Tibet: Texts in Mongghul, Chinese, and English - Li, Dechun (Translator) (World Oral Literature Series, 2017)
Containing ballads of martial heroism, tales of tragic lovers and visions of the nature of the world, Long Narrative Songs from the Mongghul of Northeast Tibet: Texts in Mongghul, Chinese, and English is a rich repository of songs collected amongst the Mongghul of the Seven Valleys, on the northeast Tibetan Plateau in western China. These songs represent the apogee of Mongghul oral literature, and they provide valuable insights into the lives of Mongghul people-their hopes, dreams, and worries. They bear testimony to the impressive plurilingual repertoire commanded by some Mongghul singers: the original texts in Tibetan, Mongghul, and Chinese are here presented in Mongghul, Chinese, and English. The kaleidoscope of stories told in these songs include that of Marshall Qi, a chieftain from the Seven Valleys who travels to Luoyang with his Mongghul army to battle rebels; Laarimbu and Qiimunso, a pair of star-crossed lovers who take revenge from beyond the grave on the families that kept them apart; and the Crop-Planting Song and the Sheep Song, which map the physical and spiritual terrain of the Mongghul people, vividly describing the physical and cosmological world in which they exist. This collection of songs is supported by an Introduction by Gerald Roche that provides an understanding of their traditional context, and shows that these works offer insights into the practices of multilingualism in Tibet. Long Narrative Songs from the Mongghul of Northeast Tibet is vital reading for researchers and others working on oral literature, as well as those who study Inner Asia, Tibet, and China's ethnic minorities. Finally, this book is of interest to linguistic anthropologists and sociolinguists, particularly those working on small-scale multilingualism and pre-colonial multilingualism.